Risk of HCC With Hepatitis B Viremia Among HIV/HBV‐Coinfected Persons in North America. Issue 3 (22nd June 2021) - Kim, H. Nina; Newcomb, Craig W.; Carbonari, Dena M.; Roy, Jason A.; Torgersen, Jessie; Althoff, Keri N.; Kitahata, Mari M.; Reddy, K. Rajender; Lim, Joseph K.; Silverberg, Michael J.; Mayor, Angel M.; Horberg, Michael A.; et al.
Abstract : Background and Aims: Chronic HBV is the predominant cause of HCC worldwide. Although HBV coinfection is common in HIV, the determinants of HCC in HIV/HBV coinfection are poorly characterized. We examined the predictors of HCC in a multicohort study of individuals coinfected with HIV/HBV. Approach and Results: We included persons coinfected with HIV/HBV within 22 cohorts of the North American AIDS Cohort Collaboration on Research and Design (1995‐2016). First occurrence of HCC was verified by medical record review and/or cancer registry. We used multivariable Cox regression to determine adjusted HRs (aHRs [95% CIs]) of factors assessed at cohort entry (age, sex, race, body mass index), ever during observation (heavy alcohol use, HCV), or time‐updated (HIV RNA, CD4+ percentage, diabetes mellitus, HBV DNA). Among 8, 354 individuals coinfected with HIV/HBV (median age, 43 years; 93% male; 52.4% non‐White), 115 HCC cases were diagnosed over 65, 392 person‐years (incidence rate, 1.8 [95% CI, 1.5‐2.1] events/1, 000 person‐years). Risk factors for HCC included age 40‐49 years (aHR, 1.97 [1.22‐3.17]), age ≥50 years (aHR, 2.55 [1.49‐4.35]), HCV coinfection (aHR, 1.61 [1.07‐2.40]), and heavy alcohol use (aHR, 1.52 [1.04‐2.23]), while time‐updated HIV RNA >500 copies/mL (aHR, 0.90 [0.56‐1.43]) and time‐updated CD4+ percentage <14% (aHR, 1.03 [0.56‐1.90]) were not. The risk of HCC was increased with time‐updated HBV DNA >200 IU/mL (aHR, 2.22 [1.42‐3.47]) and was higher with each 1.0 log10 IU/mL increase in time‐updated HBV DNA (aHR, 1.18 [1.05‐1.34]). HBV suppression with HBV‐active antiretroviral therapy (ART) for ≥1 year significantly reduced HCC risk (aHR, 0.42 [0.24‐0.73]). Conclusion: Individuals coinfected with HIV/HBV on ART with detectable HBV viremia remain at risk for HCC. To gain maximal benefit from ART for HCC prevention, sustained HBV suppression is necessary.